Aplicações fluviológicas na planície do alto rio Paraná (PR-MS). - Arenas Ibarra, José Antonio (2008)
This thesis was performed using approaches of what has been called "fluviology", the study of fluvial systems considering approaches came from biology, hydrology, geomorphology and from all science that contributes to our better understanding of riverine systems. The first article, "Hydrological connectivity in the upper Parana fluvial macrosystem: influence of upstream dams" focuses on the influence of upstream reservoirs in the hydrological connectivity in upper Parana fluvial macrosystem. Hydrometric time series of Porto São José station (PR) was divided into four periods: 1964 -1971 (natural period), 1972-1981, 1982-1997 and 1998-2007. The connectivity levels of 3.5 m. and 15000 m3/s were considered, providing several variables of the FITRAS function and related indices, calculated from hydrometric records that were analyzed by ANOVA. Changes were evident after 1964-1971 intensified after 1998-2007, period of closure and functioning of the closer dam to the macrosystem. These changes occurred in both levels considered, being more evident in the level of 15000 m3/ s. The conclusion is that connectivity between the main course of Parana river and its floodplain was modified influenced by the operation of dams located upstream of the stretch studied, compromising the functioning of macrosystem and biology of the its species. The second article, "Landscape structure in the State Park of Ivinhema?s river Varzeas and its importance for the conservation of fluvial macrosystems" landscape diversity and hydrologic attributes were evaluated in three sectors of the State Park of Ivinhema?s river Varzeas aiming related them. The sectors considered were Baia- Ipoitã Channel (BAIA-IPO), Ipoitã Channel-Ivinheminha (IVINH) and Ivinheminha- 3rd mouth of Ivinhema river (FOZ). The determination of landscape diversity was made on Landsat 7 TM image (09/08/00), classified according to the patches of water, exposed soil, shrub / grassland vegetation, fluvial forest and flooding basin. Landscape composition indexes of richness, diversity, equitability and dominance were considered. Hydrologic attributes of f FITRAS were calculated for the three geographic points of minor altitude at each sector. BAIA-IPO sector had the biggest richness and dominance with shrub vegetation/ grassland patches predominantly. IVINH sector showed the highest diversity, equitability and largest flooded area. BAIA-IPO and FOZ sectors had differences in the f FITRAS attributes. Geomorphology and the regime of pulses strongly influenced the landscape composition in fluvial macrosystem. These factors should be considered for the management of conservation units that include fluvial macrosystems river in its area.